2012
DOI: 10.1111/j.1443-1661.2012.01333.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposed blood vessels of more than 2 mm in diameter are a risk factor for rebleeding after endoscopic clipping hemostasis for hemorrhagic gastroduodenal ulcer

Abstract: Endoscopic clipping monotherapy is effective for hemorrhagic gastroduodenal ulcers; however, exposed blood vessels of more than 2 mm in diameter in the initial endoscopic procedure are a risk factor for rebleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…Risk factors for early rebleeding include unstable hemodynamic status, severe anemia (Hb <8 g/dL), active bleeding (Forrest Ia/Ib), large‐sized ulcer >2 cm, hematemesis, and exposed blood vessels >2 mm in diameter. Patients with a white, protruded and peripheral non‐bleeding visible vessel (Forrest IIA) also have a high risk of rebleeding . From the above, second‐look endoscopy should be carried out in patients with a high risk of rebleeding when PPI therapy is given after initial hemostasis (evidence level IVb, recommendation C1).…”
Section: Management Of Patients With Acute Peptic Gastroduodenal Ulcementioning
confidence: 99%
See 3 more Smart Citations
“…Risk factors for early rebleeding include unstable hemodynamic status, severe anemia (Hb <8 g/dL), active bleeding (Forrest Ia/Ib), large‐sized ulcer >2 cm, hematemesis, and exposed blood vessels >2 mm in diameter. Patients with a white, protruded and peripheral non‐bleeding visible vessel (Forrest IIA) also have a high risk of rebleeding . From the above, second‐look endoscopy should be carried out in patients with a high risk of rebleeding when PPI therapy is given after initial hemostasis (evidence level IVb, recommendation C1).…”
Section: Management Of Patients With Acute Peptic Gastroduodenal Ulcementioning
confidence: 99%
“…Interventional radiology (IVR) or surgery should be carried out in patients with peptic gastroduodenal ulcer bleeding in whom endoscopic hemostasis fails (evidence level IVb, recommendation C1). Large ulcer size and the presence of hypovolemic shock are factors related to failure to achieve hemostasis in patients with recurrent bleeding after initial treatment . IVR for peptic gastroduodenal ulcer bleeding can be done with a high technical success rate (90–100%), but the clinical success rate varies from 50% to 83% .…”
Section: Management Of Patients With Acute Peptic Gastroduodenal Ulcementioning
confidence: 99%
See 2 more Smart Citations
“…The exposed vessel of the third patient had a vascular diameter that greatly exceeded 2 mm. Ishikawa et al previously reported that an exposed blood vessel with a diameter of 2 mm or more was a risk factor for recurrent bleeding [21]. According to Lin et al, the rate of recurrent bleeding is directly correlated with the size of a non-bleeding visible vessel [19].…”
Section: Discussionmentioning
confidence: 99%